2004
DOI: 10.1002/jgt.20035
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo‐random properties of self‐complementary symmetric graphs

Abstract: There are some results in the literature showing that Paley graphs behave in many ways like random graphs G(n; 1=2). In this paper, we extend these results to the other family of self-complementary symmetric graphs. ß

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…First, if m | (n − 1) then, rather than quadratic residues in F n , one may determine adjacency by means of the multiplicative subgroup of m-th powers and its cosets. Having similar quasirandom properties [2,27], such graphs proved useful in Ramsey theory [15,24,42]. They appear also in the classification of graphs with strong symmetries [32,37].…”
Section: Explicit Construction Of Ample Complexesmentioning
confidence: 99%
“…First, if m | (n − 1) then, rather than quadratic residues in F n , one may determine adjacency by means of the multiplicative subgroup of m-th powers and its cosets. Having similar quasirandom properties [2,27], such graphs proved useful in Ramsey theory [15,24,42]. They appear also in the classification of graphs with strong symmetries [32,37].…”
Section: Explicit Construction Of Ample Complexesmentioning
confidence: 99%
“…Note that M q is not closed under multiplication since g • g = g 2 / ∈ M q . Kisielewicz and Peisert [KP04] showed that Paley graphs and Peisert graphs are similar in many aspects. However, we know very little about the structure of cliques of Peisert graphs other than Theorem 2.5.…”
Section: Background and Overview Of The Papermentioning
confidence: 99%
“…We will introduce Peisert graphs formally in Section 5. Peisert graphs form a nice family of Cayley graphs defined on finite fields with square order, and they are similar to Paley graphs in many aspects (see the discussion on [32]). However, little is known about the cliques of Peisert graphs and they seem to be much harder to study compared to (generalized) Paley graphs.…”
Section: Theorem 14 ([40]mentioning
confidence: 99%
“…Theorem 5.2 (Theorem 5.1 in [32]). Let q = p 2s , where p is a prime such that p ≡ 3 (mod 4) and s is a positive integer.…”
Section: Maximum Cliques In Peisert Graphsmentioning
confidence: 99%